Differences in Anti-inflammatory Effects of Celecoxib Emulgel Preparations with Variations in Surfactant Concentration between Lecithin and Tween 80 - Achmad Quraisy Aljufri; Muhammad Ikhsan; Danang Novianto Wibowo; Afif Rahmatun Hikmah (Jurnal Ilmiah Sains, 2024)
Celecoxib is a non-steroidal anti-inflammatory drug (NSAID) which is widely used to treat inflammation such as rheumatoid arthritis and primary dysmenorrhea. The absorption of celecoxib in the body is very low when taken orally, so it can be increased by changing the route of administration via transdermal route such as emulgel. This study aims to determine the increase in the anti-inflammatory activity of celecoxib emulgel with varying concentrations of surfactants in formula with Lecithin and formula with Tween 80.  Celecoxib emulgel, was made into 3 formulas with variations in the concentration for each formula with Lecithin (FI=3%; FII=5%; FIII=7%) and Tween 80 (FI=5%; FII=10%; FIII=15%). The anti-inflammatory activity test was carried out by inducing edema in the soles of rats' feet using carrageenan. Rats were divided into 5 groups for each formula: 1) negative control, 2) without surfactant, 3) FI, 4) FII, and 5) FIII. The edema volume was measured every 1 hour for 6 hours using a plethysmometer.  Results of the anti-inflammatory test showed that the average value of AUC0-360 in the Lecithin group = 57.97-77.17 μg/hour/mL and in the Tween 80 group = 51.45-77.17 μg/hour/mL. %DAI results of formula without surfactant=9.33%, FI (Lecithin=10.01%; Tween 80=24.49%), FII (Lecithin=18.36%; Tween 80=29.05%), and FIII (Lecithin=24.88%; Tween 80=33.33%). Based on these data, it can be concluded that there is an increase in the anti-inflammatory effect of celecoxib emulgel with increasing surfactant concentration in the formula with Lecithin and in the formula with Tween 80. Keywords: Anti-inflammatory; celecoxib; emulgel; surfactant